Selfhood and uniqueness of the person (according to the Christian perspective) - González Fernández, Enrique (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The person is not alone and isolated, but in a social setting. Although I am a changing reality, not an identical one, I am the same as before, and as after; there is, therefore, an essential selfhood of the «I», which is not «identity» in the sense in which this word is applied to things, and still less the identity of ideal objects. According to this new logic and new metaphysics, I see myself as unmistakably someone, a concrete and unique person, a historical reality, not as a «something», a «who» and as such different from all the «whats», with a proper name. I feel myself to be free and therefore responsible, capable of making choices and decisions. My life is mine, and so is the life of each person; it is unique and unrepeatable. But, since Greek philosophers, there are a long series of attempts to convert humanity into a «thing»: the old logic and metaphysics (based on identity and immobility) see person as a substance.
Keywords: essence; ideal objects; identity; life; logic; metaphysics; principle of individuation; selfhood; self-sufficiency; substance; uniqueness; universals